Peningkatan Kemampuan Pemecahan Masalah Siswa Melalui Problem-Based Learning (PBL) Berbantuan Alat Peraga - Suliarti, Dela; Maulidiya, Della; Utari, Tria (Institut Agama Islam Negeri Curup, 2024)
This research aims to apply problem-based learning with a teaching props to improve the problem-solving abilities of polyhedron. This type of research is Class Action Research (PTK) that is carried out in three cycles. The subjects of this research were 32 students in class VIII 5 of SMP Negeri 4 Bengkulu City in the 2022/2023 Academic Year. Data collection is carried out through a problem-solving ability test that is structured with reference to Polya and competence achievement indicators on the cube, beam, prisma, and limas. The student understands the problem on the LKPD, then discusses the determination of their respective tasks for the work of the LKPD, the student solves the problem using the help of the teaching props according to the learning indicators, students present the results of the discussion, and the student works on the KPM using the stages of problem solving. In the indicator of understanding the problem, the average score increased from 61 (cycle I) to 88.49 (cycle III); in the indicator of planning problem-solving, the average score increased from 39 (cycle I) to 86.11 (cycle III); in the indicator of implementing the problem-solving plan, the average score increased from 40 (cycle I) to 85.12 (cycle III); and in the indicator of reviewing and drawing conclusions, the average score increased from 39 (cycle I) to 91.67 (cycle III). Students' problem-solving skills in cycle III have reached the